Metode Analisis dalam Mengungkap Komposisi Perisa Buah E-Liquid Rokok Elektrik: Sebuah Tinjauan - Nabila, Aghnia; Yuwono, Mochammad; Ma'ruf, Mochammad Taha; Zulni, Shalsa Septia (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
The use of e-cigarettes is increasing, one of which is due to fruit-flavored e-liquids. The chemical compounds that make up these flavors play a role in providing flavor characteristics, but if inhaled, they can potentially negatively affect health. Understanding what chemical compounds are found in e-liquid flavors is very important to determine the toxicity effects of e-cigarettes. This article aimed to review the analytical methods that had been carried out by previous studies in identifying e-liquid flavor compounds. Literature was collected through searches in reputable scientific databases, including ScienceDirect, Scopus, Web of Science, PubMed, and Google Scholar, using relevant keywords. From the initial search, 35 relevant articles were found and then selected based on inclusion and exclusion criteria, resulting in 10 articles for further analysis. The selected literature consisted of research focusing on chromatographic methods, specifically Gas Chromatography (GC) and Liquid Chromatography (LC). Further developments, such as the combination of GC with Mass Spectrometry (MS) and Ion Mobility Spectrometry (IMS), as well as LC with MS/MS and Electrospray Ionization (ESI), were shown to improve the sensitivity and selectivity of the analysis. These findings emphasize the importance of choosing the right analytical method for the compounds to be identified. The results also discuss the advantages and challenges, which can guide in choosing the right analytical method to promote the development of better safety standards.